Factors Influencing Consumer Purchasing Decision-Making (Case Study of the MSME Craft Industry in Yogyakarta City, Special Region of Yogyakarta Province) - Fx. Pudjo Wibowo; Eso Hernawan; Gregorius Widiyanto (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
The purpose of this study was to use a simple random sampling method to distribute questionnaires to consumers of small and medium-scale handicraft industries in Yogyakarta, Yogyakarta Special Region, to determine the influence of price, location, promotion, and service on their purchasing decisions. Price, location, promotion, and service are independent factors in this study, while consumer purchasing decisions in the MSME handicraft industry in Yogyakarta City are the dependent variables. We conducted a survey of micro, small, and medium enterprise (MSME) customers in Yogyakarta City, Yogyakarta Special Region, by sending questionnaires directly to them. Using SPSS Version 25.00 and consumer data from Yogyakarta City, Yogyakarta Special Region This study uses multiple regression analysis, coefficient of determination analysis, F test, and t test for analysis. The adjusted R2 value in this study means that the variance in decision making can be explained by price, location, promotion and service through a model of 84.4% and the remaining 15.6% comes from other variables outside the price, location, promotion and service variables. The t test shows that price (X1), location (X2), promotion (X3) and service (X4) partially have a positive and significant effect on consumer purchasing decision making in the MSME Craft Industry in Yogyakarta City, Special Region of Yogyakarta, where the calculated t value of price is 2.602. > t table 1.65 and .0011 < 0.05, the calculated t value of location is 2.111 > t table 1.65 and .0037 < 0.05, the calculated t value of promotion is 6.101. > ttable 1.65 and .0000 < 0.05 and the calculated t value of service 6.648 > ttable 1.65 and .0000 < 0.05 The F test shows a simultaneous (together) influence between price, location, promotion and service, on (consumer purchasing decision making) in the MSME Craft Industry in Yogyakarta City, Special Region of Yogyakarta, obtained the calculated F value > F table or 128,419 > 3.87 or a significance level (sig) of 0.000 <0.05.